2015
DOI: 10.1111/jgh.13014
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasonography for staging depth of invasion in early gastric cancer: A meta‐analysis

Abstract: Endoscopic ultrasonography only has a relatively low accuracy for staging the depth of invasion in EGCs. Accordingly, EUS may be not indispensable in the staging of EGCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 42 publications
4
42
1
2
Order By: Relevance
“…However, the standard imaging modality for clinical assessment of EGC remains debatable. Whether EUS is more accurate than MDCT in diagnosing EGC remains unknown [12, 15, 25]. This meta-analysis demonstrated that the sensitivity of EUS was significantly higher than that of MDCT for EGC, indicating that EUS was a preferred imaging modality in diagnosing EGC.…”
Section: Discussionmentioning
confidence: 96%
“…However, the standard imaging modality for clinical assessment of EGC remains debatable. Whether EUS is more accurate than MDCT in diagnosing EGC remains unknown [12, 15, 25]. This meta-analysis demonstrated that the sensitivity of EUS was significantly higher than that of MDCT for EGC, indicating that EUS was a preferred imaging modality in diagnosing EGC.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study [29] also showed that EUS may not be necessary before ESD, because EUS did not increase the likelihood of selecting the appropriate treatment in differentiated-type EGC. One recent meta-analysis also concluded that EUS may be not indispensable in the staging of EGCs [30]. Pit patterns observed by magnifying chromoendoscopy can be used to predict invasion in colonic lesions [31].…”
Section: Discussionmentioning
confidence: 98%
“…However, the overall diagnostic accuracy rate was 70% or lower and the sensitivity of T4 diagnosis was 48%. Most Japanese studies on the usefulness of EUS aimed to determine the indication for endoscopic submucosal dissection and, therefore, mostly covered early gastric cancer patients [28,29]. Evidence on the usefulness of EUS for determining cancer depth in T2-T4 cases remains limited.…”
Section: Discussionmentioning
confidence: 99%